Konsep Pembelajaran PAI Berbasis Multikulturalisme dengan Pendekatan Transformatif dan Keputusan Aksi Sosial - Mariani, Mariani; Mutawali, Akhmad; Cahyadi, Ani (Juwara: Jurnal Wawasan dan Aksara, 2024)
The concept of multiculturalism as a new paradigm that has a vision and program to prepare the younger generation to face the global world society in a multicultural framework. In responding to the development of the era in the 2st century, Islamic Religious Education learning is not only to maintain harmony but also to make the students go into the field to see community problems and can provide social action or social change. This study aims to describe the concept of Islamic Religious Education learning with a transformative and social action decisions. Thisy study uses a library research with a qualitative approach. The results of this study indicated that these two approaches are more recommended to be implemented in senior high school or higher education (universities) because these concepts require emotion and cognition to see the different conditions of society and can go into the fileds to make social changes. In addition, an Islamic Religious Education learning design is also needed that is relevant to the spirit of diversity. As an implication of this study, the authors suggest that the importance of providing multicultural insight for Islamic Religious Education teachers.